Pendekatan Analisis Dalam Konteks Keuangan, Sumber Daya Manusia, dan Pemasaran - Burhanuddin, Burhanuddin (Journal Management & Economics Review (JUMPER), 2024)
This research aims to analyze organizational behavior in the context of finance, human resources, and marketing. An analytical approach is used to understand how these factors interact and influence the overall performance of the organization. The research methodology involves both quantitative and qualitative data analysis, collecting information through surveys and interviews with employees, as well as analyzing financial and marketing data. The results of the research indicate a relationship between effective financial policies, good human resource management, and appropriate marketing strategies with good organizational performance. In this context, it is important to integrate these aspects to effectively achieve organizational goals. This research provides new insights into how organizational behavior can be applied in the context of finance, human resources, and marketing to enhance organizational performance.